A New T-287C Polymorphism in the 5’ Regulatory Region of the Tissue Factor Pathway Inhibitor Gene - Moatti, Didier; Haidar, Bassam; Fumeron, Frédéric; Gauci, Laurent; Boudvillain, Olivier; Seknadji, Patrick; Ollivier, Véronique; Aumont, Marie Claude; de Prost, Dominique (Thrombosis and Haemostasis, 2000)
Tissue factor pathway inhibitor (TFPI) is an important regulator of the extrinsic blood coagulation pathway. We screened the untranslated 5’ region of the TFPI gene for polymorphisms and investigated their possible involvement in arterial thrombosis. The allele frequencies of a new polymorphism, located 287 base pairs upstream of the transcription start site (T-287C), and that of the previously described C-399T polymorphism, were similar in cases and controls. In controls, the -287C allele was associated with significantly higher levels of total TFPI antigen, arguing for an effect of this polymorphism on TFPI gene expression. In controls, the C-399T polymorphism did not alter TFPI levels. In the cases, however, decreased total and post-heparin free TFPI levels and increased F1+2 levels were significantly associated with the -399T allele. These findings suggest that the T-287C and C-399T polymorphisms are not associated with an increased risk of coronary heart disease, a result which should be confirmed by a larger study. However, their influence on outcome, or a link with subtypes of acute coronary syndromes, cannot be excluded.
Keywords: Tissue factor pathway inhibitor; polymorphism; promoter; myocardial infarction; unstable angina